2020
DOI: 10.25259/cjhs_15_2019
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and some heavy metals analysis of smoked fishes sold in urban and rural markets in Akwa Ibom State, Nigeria

Abstract: Objective: The unhygienic nature of our local markets, including fish handlers, may contribute to the presence of microorganisms in smoked fish leading to food poisoning. Furthermore, heavy metals can find their way into the food chain through fish raising public health concerns. This study assessed the microbial load and some heavy metals in smoked fishes (bongafish and catfish) sold in urban and rural markets in Akwa Ibom State, Nigeria. Materials and Methods: Standard microbiological techniques and analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
2
10
0
2
Order By: Relevance
“…Several authors reported the presence of trace elements in smoked fish (Anigboro et al., 2011 ; Ibanga et al., 2019 ; Inobeme et al., 2018 ). Şireli et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors reported the presence of trace elements in smoked fish (Anigboro et al., 2011 ; Ibanga et al., 2019 ; Inobeme et al., 2018 ). Şireli et al.…”
Section: Resultsmentioning
confidence: 99%
“…The studies on the occurrence of heavy metals in smoked or grilled fish and meat reported in this section were mainly from Africa. Indeed, although some studies were from Turkey (Ersoy et al., 2006 ; Şireli et al., 2006 ), Spain (Perello et al., 2008 ) and Poland (Rajkowska‐Myśliwiec et al., 2021 ), the majority of them were from Nigeria (Amos‐Tautua et al., 2013 ; Anigboro et al., 2011 ; Aremu et al., 2014 ; Daniel et al., 2013 ; Ersoy et al., 2006 ; Ibanga et al., 2019 ) and other African countries such as Egypt (Abbas et al., 2021 ), Ghana (Kobia et al., 2016 ) and Burkina Faso (Bazié et al., 2021 ). Heavy metals contamination data (Table 5 ) showed that before 2015 (2006–2014) many studies from different countries especially Turkey and Nigeria were carried out on the occurrence of these environmental contaminants in smoked or grilled fish and meat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Proteus mirabilis were the bacteria isolates associated with smoked fish from Bida modern market Niger state. Similarly, the presence of this groups of bacteria's have also been reported in the bacteriological assessment of some fresh and smoked catfish in Nigeria [2,[10][11][12][13] . The present of most of this species of bacteria can be attributed to contamination of sampled fish by man through handling and processing [14] .…”
Section: Discussionmentioning
confidence: 70%
“…The bacterial colony counts result of catfish in Bida modern market shows a mean value of 1.84×10 6 cfu/g, this high population of bacterial colony could be due to poor or unhygienic conditions of the environment in which the fish samples were processed, packaged and preserved [11] , and also personal hygiene of the fish handlers [1,2,10] . Also, gross contamination of the fishes can be attributed to means or source of transport employed in transporting the fishes from their sources and processing to the market as they are exposed to dust and other environmental issues [12,13] . The result of the present study revealed a total of seven bacteria species consisting of four (4) gram-positive bacteria and three (3) gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%